Relationship Between Over-Controlling Parenting and Flourishing: A Mediation Model - Pierce, Hannah F. (My University, 2025)
Emerging adulthood (18-25 years) is a unique developmental period where many individuals are figuring out who they are and (potentially) exploring different opportunities to build their identities (Arnett, 2000). Many within this age group are struggling with depression and anxiety (Browning et al., 2021; Conrad et al., 2021), and this study wants to explore why. Previous research has shown over-controlling parenting was associated with baseline personality disorder symptoms (Johnson, et al., 2011) and may impede the child’s ability to develop independence and decision-making skills (Perry et al., 2018) as well as to flourish (Toman et al., 2024). In addition, research has shown perceived parental psychological control and insecure attachment styles are negatively related to independent decision-making (Xiang & Liu, 2018). I hypothesized perceived parental psychological control would be negatively related to flourishing due to an increase in insecure attachment styles (i.e., anxious-preoccupied, fearful-avoidant, dismissive-ambivalent) and mental health factors (i.e., anxiety, depression, personality disorder symptomatology). To test this, participants took a survey that measured each of our variables through seven well-supported questionnaires. 164 participants were included with 56.7% not enrolled in college and 26.3% enrolled in their first year at a large Midwestern university. Our results indicated perceived parental psychological control is negatively related flourishing due to increased levels of depression, anxiety, and an anxious-preoccupied attachment style.